Implementasi Pembelajaran Berbasis Riset, dan Media CTP Pada Pembelajaran Sains: Upaya Mengembangkan Keterampilan Menulis Ilmiah Mahasiswa - Syazali, Muhammad; Widiada, I Ketut; Rahmatih, Aisa Nikmah; Hasnawati, Hasnawati; Hayati, Ilmi Solihana; Elvira, Baiq Olivia Dwita (Jurnal Ilmiah Profesi Pendidikan, 2025)
The results of the paper quality assessment show that students' writing skills are still relatively low. This fact is that the number of learning facilities is directly proportional to the writing skills that can be achieved by students. The goal is to analyze the quality of students' science research papers through the implementation of these learning facilities. This pre-experiment research will be conducted on students of PGSD Study Program, FKIP, Mataram University. The sample size is determined by purposive sampling. To obtain data, paper documents are assessed using an assessment rubric. There are a total of 23 indicators that are used as a reference to get a score. The scores obtained from these activities are converted into scores that range from 0 - 100. To get an overview of student skills, data analysis using descriptive statistics was conducted. This includes averages and proportions/percentages. As for comparing the effectiveness of the treatment on. The results of the study show that the degree of mastery of students in writing papers is at a quantitative value of 83.47. This quantitative value has an A grade. In addition, the median of the quantitative data is 83.18. This indicates that at least 50% of students have excellent writing skills. The mode value is even higher at 85.00 with a proportion of 29%. Comparative analysis shows a significant difference with p < 0.05, reinforcing the effectiveness of the PBR model combined with learning media. The t-value, ranging from 9.761 to 25.657, indicates that the difference is highly significant and not coincidental. From this data, it can be concluded that the implementation of the PBR model assisted by CTP media is effective in developing the scientific writing skills of PGSD students.